A good debutante's guide to ruin - Jordan, Sophie, author. (New York : Avon, an imprint of HarperCollinsPublishers)
When her newfound stepbrother, Declan, lands her with a dowry whose vastness makes her the target of fortune hunters, Rosalie Hughes seeks a man who wants her and not her money, but finds herself drawn to the infuriating Declan.